2023
DOI: 10.3389/fmicb.2023.1120048
|View full text |Cite|
|
Sign up to set email alerts
|

Specific TLR-mediated HSP70 activation plays a potential role in host defense against the intestinal parasite Giardia duodenalis

Abstract: Giardia duodenalis, an important flagellated noninvasive protozoan parasite, infects the upper small intestine and causes a disease termed giardiasis globally. Few members of the heat shock protein (HSP) family have been shown to function as potential defenders against microbial pathogens, while such information is lacking for Giardia. Here we initially screened and indicated that in vitro Giardia challenge induced a marked early upregulation of HSP70 in intestinal epithelial cells (IECs). As noted previously,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…Autophagy and apoptosis are biologically linked as discussed previously ( 80 ). Although our recent studies have demonstrated Giardia -induced TNFR1-mediated extrinsic and ROS-mediated mitochondrial pathways of apoptosis in Caco-2 and HT29 cells ( 43 , 44 , 48 ), the interplay between autophagy and apoptosis in IECs, notably primary epithelial cells, during noninvasive Giardia infections is still unknown and is not elucidated under the present circumtances, and therefore needs to be further investigated.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Autophagy and apoptosis are biologically linked as discussed previously ( 80 ). Although our recent studies have demonstrated Giardia -induced TNFR1-mediated extrinsic and ROS-mediated mitochondrial pathways of apoptosis in Caco-2 and HT29 cells ( 43 , 44 , 48 ), the interplay between autophagy and apoptosis in IECs, notably primary epithelial cells, during noninvasive Giardia infections is still unknown and is not elucidated under the present circumtances, and therefore needs to be further investigated.…”
Section: Discussionmentioning
confidence: 82%
“…Giardia -induced early-stage autophagy was then biologically linked to TJ/NO regulation in IECs, and this link was proven to be closely associated with ROS-dependent AMPK/mTOR signaling. Although in vitro models of interaction between Giardia and IECs (Caco-2 and HT29) has also been widely applied previously ( 46 , 48 , 56 59 ), the present observations need to be further clarified by in vivo studies. However, effective in vivo models of Giardia infection by WB isolate are still lacking since modeling human giardiasis in animals is complicated and difficult.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation